Curcumin-Piperlongumine Hybrids with a Multitarget Profile Elicit Neuroprotection in In Vitro Models of Oxidative Stress and Hyperphosphorylation - Ángel Cores; Noelia Carmona-Zafra; Olmo Martín-Cámara; Juan Domingo Sánchez; Pablo Duarte; Mercedes Villacampa; Paloma Bermejo-Bescós; Sagrario Martín-Aragón; Rafael León; J. Carlos Menéndez (Antioxidants, 2021)
Curcumin shows a broad spectrum of activities of relevance in the treatment of Alzheimer’s disease (AD); however, it is poorly absorbed and is also chemically and metabolically unstable, leading to a very low oral bioavailability. A small library of hybrid compounds designed as curcumin analogues and incorporating the key structural fragment of piperlongumine, a natural neuroinflammation inhibitor, were synthesized by a two-step route that combines a three-component reaction between primary amines, β-ketoesters and α-haloesters and a base-promoted acylation with cinnamoyl chlorides. These compounds were predicted to have good oral absorption and CNS permeation, had good scavenging properties in the in vitro DPPH experiment and in a cellular assay based on the oxidation of dichlorofluorescin to a fluorescent species. The compounds showed low toxicity in two cellular models, were potent inductors of the Nrf2-ARE phase II antioxidant response, inhibited PHF6 peptide aggregation, closely related to Tau protein aggregation and were active against the LPS-induced inflammatory response. They also afforded neuroprotection against an oxidative insult induced by inhibition of the mitochondrial respiratory chain with the rotenone-oligomycin A combination and against Tau hyperphosphorylation induced by the phosphatase inhibitor okadaic acid. This multitarget pharmacological profile is highly promising in the development of treatments for AD and provides a good hit structure for future optimization efforts.